2021
DOI: 10.33732/ixc/11/02mapeod
|View full text |Cite
|
Sign up to set email alerts
|

Mapeo del consumo de medios en los jóvenes: redes sociales, 'fake news' y confianza en tiempos de pandemia

Abstract: The explosion of the Covid-19 pandemic has led to a major transformation in media consumption and the use of social networks. New habits and extensive exposure to connected devices coupled with unmanageable amounts of information warn of a worrying reality, especially among the younger population. The aim of this research is to discover the degree of trustworthiness of Generation Z towards the media, their media consumption preferences and the association they make between media consumption and fake news. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
6
0
3
Order By: Relevance
“…In terms of the second objective of this work, I was interested in illuminating the relationship between the political information consumption habits of college students and their perceptions and interactions with disinformation. In agreeance with previous works (Pérez-Escoda et al, 2021;Perez-Escoda & Pedrero Esteban, 2021), results of this research indicate that, although they say they find more disinformation there, college students still significantly prefer social media over traditional channels. However, when inquiring about the content they consume on social media platforms, participants pointed out that, along with new digital media or influencers who have become opinion leaders, they also follow verified accounts of established media outlets they trust.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of the second objective of this work, I was interested in illuminating the relationship between the political information consumption habits of college students and their perceptions and interactions with disinformation. In agreeance with previous works (Pérez-Escoda et al, 2021;Perez-Escoda & Pedrero Esteban, 2021), results of this research indicate that, although they say they find more disinformation there, college students still significantly prefer social media over traditional channels. However, when inquiring about the content they consume on social media platforms, participants pointed out that, along with new digital media or influencers who have become opinion leaders, they also follow verified accounts of established media outlets they trust.…”
Section: Discussionsupporting
confidence: 92%
“…Young people are the ones that most report using social media to get information while increasingly distancing themselves from conventional sources, such as television, print newspapers, and radio (Pérez-Escoda et al, 2021). Knowing their attitudes and perceptions vis á vis disinformation is therefore of great interest, given that such content is highly present on the digital platforms they prefer.…”
Section: Fake News and Young People's Consumption Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…La detección de tendencias y la escucha social son de suma importancia para el periodismo, en parte por las audiencias prosumidoras (Papacharissi, 2012) y porque un mayor flujo informativo es susceptible de mayor desinformación (Damián et al, 2020;Pérez-Escoda et al, 2021), aunque también por la necesidad de segmentar mucho mejor al público y delimitar así los puntos de interés de cada audiencia (Matellanes, 2011). De este modo, se procura una mejor conexión entre el medio y el público y, por tanto, se preserva la sostenibilidad del modelo de subsistencia de los medios y periodistas a través de suscripciones y comunidades a partir de contenidos con valor agregado, mayor participación, experiencias diferenciadas y plataformización (Sidorenko et al, 2020).…”
Section: Ia En Redacciones Y Medios Y La Detección De Informaciónunclassified
“…In this sense, interventions in media literacy can reduce such discontent ( 17 ). A study conducted in Spanish universities about media consumption by young people identified that social media is the primary source of information and, simultaneously, the least reliable source, leading to the dissemination of fake news ( 18 ). Thus, there is a lack of media literacy from a critical perspective, even among university students ( 18 ).…”
Section: Introductionmentioning
confidence: 99%